Біоморфогенез Crambe koktebelica (Junge) N. Busch в умовах Карадазького природного заповідника - Kalista, M.S.; Scherbakova, O.F. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2012)
The biomorphological peculiarities and polyvariant biomorphogenesis of the rare endemic species – Crambe koktebelica (Junge) N. Busch were studied in Karadag Nature Reserve of the NAS of Ukraine.